Upper Silurian stromatoporoids from Somerset Island, Arctic Canada - Savelle, James M. (Canadian Journal of Earth Sciences, 1979)
Plexodictyon katriense Nestor, P. heclae n. sp., Diplostroma sp., Actinostroma furyi n. sp., Actinodictyon netsiliki n. sp., and Vicinostachyodes sokolovi (Riabinin) occur in Upper Silurian (middle to late Ludlovian) strata near Creswell Bay, Somerset Island. Faunal and sedimentological evidence suggests the stromatoporoids inhabited predominantly shallow, high energy, near-shore environments.